Peran Satuan Kerja Audit Internal Dalam Mendeteksi Fraud Pada Perbankan Syariah Di Indonesia - Rito Rito; Mulyaning Wulan; Adityo Ari Wibowo (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Sharia Banking in Indonesia continues to strive to be able to maintain transparency and prevent fraud. The audit committee is a tool for the board of commissioners to help maintain the professionalism of the bank. Also Internal Audit or Unit of Work of Internal Audit (SKAI) in Sharia banking is needed to ensure that the company is operating in accordance with the Bank's Regulations and operational standards owned by each bank. Based on the International Standards for the Professional Practice of Internal Auditing, internal audit has a consulting and assurance role. Therefore, internal audit must have the skills, professional, independent and objective in carrying out its role. As one of the roles of assurance, internal audit can detect fraud. Fraud is an act of cheating that can be done by many groups, ranging from employees to top management that can harm the stakeholders. Several factors cause fraud, namely arrogance, competence, opportunity, pressure and rationalization. Types of fraud that can occur are corruption, misuse of assets, manipulation of financial statements and cybercrime.